Design Any Disaster : the revolutionary blueprint to master your next crisis or emergency - Hardy, Patrick (Founder and CEO of Hytropy Disaster Management) (Dallas: BenBella Books, 2023)
"In Design Any Disaster, Hardy will equip you with the critical mindset and practical tools you need to respond to any emergency"--
Includes bibliographical references and index.
Keywords: Crisis Management; Communication in Management